Preserving the Feitao ritual in an era of globalization: the heritage ecology of Maonan ethnic minority in modern China - Yixing, Liu; Ow Wei, Chow (Tarun Tapas Mukherjee, 2024)
This article examines the dynamics of the Feitao ritual, a traditional practice of the Maonan ethnic minority, within the broader context of globalization and heritagization in China. It addresses the challenge of preserving the cultural identity and memory of ethnic minorities amidst economic development imperatives, a dilemma common to many late-developing countries. By focusing on transforming the Feitao ritual from a communal practice to a performative spectacle, this study unravels the intricate process of heritage ecology within minority rituals. Utilizing a combination of ethnological fieldwork and interviews, this article explores the perceptions and approaches toward the post-heritagization of the ritual among the Maonan community members and policymakers. It also emphasizes on the evolution of the ritual into a significant tourist attraction, showcasing the performative transformation of religious practices by an ethnic minority in China. The central argument of this article is that this ritual is formed in ecological interactions; it also symbolizes a self-defense for the rights and a pursuit of recognition for a minority group. It has been a vital medium for the Maonan people to construct and uphold a positive self-perception. This study endorses a faith-aware and community memory-focused approach to preserve the cultural heritage of ethnic minorities. The authors contend that this approach is essential to safeguard the cultural memory and identity of minorities in developing countries like China against the homogenizing forces brought by globalization in China.